Mechanical, thermal, and flammability behaviour of low density polyethylene - oil based mud fillers nanocomposites. - Siddique, Shohel; Smith, Grant David; Yates, Kyari; Njuguna, James
Novel low density polyethylene (LDPE)/Oil based mud fillers (OBMF) nanocomposites were manufactured by a melt compounding process. Fourier Transform Infrared (FTIR) Spectroscopy was used to characterise the structure of the nanocomposites. The results revealed the influence of different clay minerals present in OBMFs in forming chemical bonds within microstructures. Scanning electron microscope (SEM) and Energy Dispersive X-Ray Analysis (EDXA) confirmed the materials were nanocomposites and also provided the elemental composition of the filler and nanocomposites. Thermal properties were investigated by Differential Scanning Calorimetry (DSC) and Thermogravimetric Analysis (TGA). The char yields of nanocomposites increased with OBMFs content. The TD5% (onset degradation temperature at 5 weight% loss) of the LDPE nanocomposite with 10.0 wt% OBMFs was 4° c higher than that of neat LDPE. Limiting Oxygen Index (L.O.I.) and UL94 tests revealed that the nanocomposites possess excellent flame retardancy which increased with increasing percentage of OBMFs. Tensile and flexural tests were also conducted which showed there was not any significant effect of OBMFs on tensile strength and flexural modulus of the nanocomposites and thereby offering an alternative material choice.
COMPLETED – Rec'd permission from JN who is co-editor of conference 6/9/2018 LM – Info via contact 3/9/2018 LM ADDITIONAL INFORMATION: Siddique, Shohel ; Njuguna, James ; Yates, Kyari – Panel B
Keywords: Nanocompoites; Mechanical; Thermal; Flammability; Oil based; Mud fillers